Pathophysiological mechanisms underlying antipsychotic-induced tardive dyskinesia - E. E. Vayman; N. A. Shnayder; N. G. Neznanov; R. F. Nasyrova (Бюллетень сибирской медицины)
Purpose. To analyze the results of classical and modern studies reflecting the pathophysiological mechanisms of antipsychotic-induced tardive dyskinesia.Materials and methods. We searched for full-text publications in Russian and English in the databases of E-Library, PubMed, Web of Science and Springer published over the past decade, using keywords (tardive dyskinesia (TD), drug-induced tardive dyskinesia, antipsychotics (AP), neuroleptics, typical antipsychotics, atypical antipsychotics, pathophysiology, etiology and combinations of these words). In addition, the review included earlier publications of historical interest.Results. The lecture proposed theories of development of AP-induced TD, examining its effect on dopaminergic receptors, dopaminergic neurons, neurons of the basal ganglia, and other theories: activation of estrogen receptors, disorders of melatonin metabolism, disorders of the endogenous opioid system, oxidative stress with predominant oxidation processes, blockade of 5-HT2-receptors, a decrease in the pyridoxine level, genetic predisposition, interaction of AP with the brain trace element – iron, carbonyl stress and immune inflammation and the role of the neurotrophic factor.Conclusion. The disclosure of the mechanisms of AP-induced TD will allow the development of a strategy for personalized prevention and therapy of the considered neurological complication of the AP-therapy for schizophrenia in real clinical practice.